2018
DOI: 10.1007/s11695-018-3455-x
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Visceral Adipose Tissue after Roux-en-Y Gastric Bypass Is more Pronounced in Patients with Impaired Glucose Metabolism

Abstract: PurposeVisceral adipose tissue (VAT) is associated with cardiometabolic risk factors and insulin resistance. The physiological mechanisms underlying the benefits of Roux-en-Y gastric bypass surgery (RYGB) on glucose metabolism remain incompletely understood. The impact of RYGB on VAT was assessed among three groups of patients stratified by their glucose tolerance before surgery.MethodsForty-four obese women were categorized into normoglycemia (n = 21), impaired glucose tolerance (IGT, n = 18) and diabetes (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…If greater VAT accumulates within the DXA ROI, then DXA’s estimates would be larger; whereas, if the excess VAT falls outside the ROI, then DXA’s estimates would be smaller. We do not believe that menopausal transition affected our finding because our estimate of VAT by DXA 12 months after surgery matches that which has been reported in other studies of women of perimenopausal age (25). Future studies should assess menopausal status when evaluating changes in VAT by DXA.…”
Section: Discussionsupporting
confidence: 82%
“…If greater VAT accumulates within the DXA ROI, then DXA’s estimates would be larger; whereas, if the excess VAT falls outside the ROI, then DXA’s estimates would be smaller. We do not believe that menopausal transition affected our finding because our estimate of VAT by DXA 12 months after surgery matches that which has been reported in other studies of women of perimenopausal age (25). Future studies should assess menopausal status when evaluating changes in VAT by DXA.…”
Section: Discussionsupporting
confidence: 82%
“…We described a higher VAT in operated women with T2D at the time of surgery as compared to non-diabetic. Previous studies reported that diabetic patients have greater amount of VAT before surgery compared to normoglycaemic subjects (7). These data highlight the association between fat distribution and T2D, even later after surgery, via the well-known lipolytic and pro-inflammatory profile of the VAT.…”
Section: Discussionsupporting
confidence: 63%
“…Body composition analysis was assessed in both groups using Lunar iDXA (GE Healthcare, Madison, WI, USA) (7). Participants were placed centered on the scanning field in a supine position, with palms down and arms at sides, slightly separated from the trunk.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first year, coinciding with the rapid weight loss phase after BS, both SAT [ 126 , 127 , 128 , 129 , 130 ] and VAT [ 126 , 127 , 128 , 129 , 130 , 134 , 135 ] depots progressively reduce their size, and this is accompanied by a reduction in the area of subcutaneous [ 136 , 137 , 138 ] and visceral [ 138 ] adipocytes, respectively. A large adipocyte size was independently associated with a lower incidence of insulin resistance 6 months after RYGBP [ 136 ].…”
Section: Bariatric Surgery—related Changes In White Adipose Tissue Biologymentioning
confidence: 99%